Proton nuclear magnetic resonance identification and discrimination of side chain isomers of phytosterols using a lanthanide shift reagent. - T Iida; T Tamura; T Matsumoto (Journal of Lipid Research, 1980)
Proton nuclear magnetic resonance (1H-NMR) spectra at 90 MHz were measured for a number of side chain isomers of phytosterols (sterols with a C8H17 side chain, and delta 24-, 24-methylene, delta 22-, 24-ethylidene, 24-methly, 24-ethyl, 24-methyl-delta 22-, 24-ethyl delta 22-, and 24-ethyl-delta 22,25(27)-sterols) with or without a lanthanide shift reagent, tris[1,1,1,2,2,3,3 - heptafluoro - 7,7 - dimethyloctane - 4,6 - dionato]ytterbium, Yb(fod)3, and the effect of Yb(fod)3 on the side chain methyl protons is discussed. The change of the chemical shifts induced Yb(fod)3 for the side chain methyls was expressed in terms of the induced shift ratios (ISR values), i.e., the ratios of the induced chemical shifts of the respective side chain methyls to that of the fastest moving side chain methyl. The ISR values were sentitive to minor structural and stereochemical differences, but almost independent of ring structures and of substrate concentrations, thus providing confirmatory evidence for the side chain structures. Also, the Yb(fod)3-induced spectral patterns observed in the high-field methyl region bore the fingerprints of the side chain structures. Several isomeric pairs of sterols, which differ only in the geometry of double bonds or the absolute configuration at C-24 in the side chain, i.e., cis- and trans-isomers of delta 22-and 24-ethylidene sterols, 24R/alpha- and 24S/beta-methyl sterols, 24R/alpha- and 24S/beta-ethyl sterols, and 24S/alpha- and 24R/beta-ethyl-delta 22-sterols, could be differentiated from each other under the influence of Yb(fod)3, even though they were measured at 90 MHz.